Analysis of the Influence of Product Quality, Service Quality, and Sales Promotion on Purchasing Decisions and Consumer Loyalty (A Case Study on Dunkin’ Indonesia Consumers) - Ramadhani, Novita Puspa; Waluyo, Minto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The number of restaurant and franchise companies in Indonesia makes people more selective in choosing products that suit what they want. In this case, companies are required to be careful in developing marketing strategies in order to spur competitiveness to win market competition. Therefore, this research tries to find out the influence of product quality, service quality, and sales promotion on purchasing decisions that have an impact on consumer loyalty and strategies to improve Dunkin’ consumer purchasing decisions. The research’s methodology is the Structural Equation Modeling (SEM) method and SWOT analysis with a sample size of 100 responders. The outcomes of this research show that product quality has a positive and significant effect on purchasing decisions, service quality cannot be proven because it is excluded from the research model, sales promotion has a negative and insignificant effect on purchasing decisions, and purchasing decisions have a positive and significant effect on consumer loyalty. The simultaneous equation obtained is Y1 = 0.367 X1 + (-0.024) X3 + Z3 and Y2 = 0.117 X1 + (-0.008) X3 + Z4. The strategy obtained from the SWOT analysis outcomes and can be applied by Dunkin’ is to implement the W-O strategy which consists of: (1) Dunkin’ can conduct market research to find the right target market and adjust their sales promotion strategy to the preferences of that target market; (2) Dunkin’ can take advantage of technology and digitalization to increase customer convenience and strengthen brand engagement.